Socjodynamiczna analiza prognoz demograficznych Polski do roku 1980 - Kossecki, Józef (Wydział Prawa i Administracji UAM, 1971)
The subject of this work is a short discussion of the demographic prognosis for Poland till the year 1980 worked out by means of traditional methods and their analysis by the sociodynamic method. First the basic conception of the sociodynamic method of investigation of social processes are presented, followed by a short discussion on the most representative demographic prognosis for Poland till the year 1980 elaborated by traditional methods. A sociodynamic analysis of demographic phenomena in Poland during 1950 - - 1969 is presented together with some conclusions, on the basis of which an appreciation of the reality of demographic prognosis is worked out by traditional methods. Finally the prognosis of births and of the population of Poland till the year 1980 is given — on the assumption that the demographic activity of the Polish society will not be altered.
Sociodynamic Analyzis of the Demographic Prognosis for Poland till the Year 1980